Polymer conjugated graphene-oxide nanoparticles impair nuclear DNA and Topoisomerase I in cancer. Issue 12 (21st November 2019) - Nandi, Aditi; Ghosh, Chandramouli; Basu, Sudipta
Abstract : Polymer modified self-assembled graphene oxide nanoparticles are developed for targeting cancer cells. Abstract : Cancer chemotherapy had been dominated by the use of small molecule DNA damaging drugs. Eventually, the emergence of DNA damage repair machinery in cancer cells has led to combination therapy with the DNA topology controlling enzyme, topoisomerase I inhibitor along with DNA impairing agents. However, integrating multiple drugs having diverse water solubility and hence bio-distribution effectively for cancer treatment remains a significant challenge, which can be addressed by using suitable nano-scale materials. Herein, we have chemically conjugated graphene oxide (GO) with biocompatible and hydrophilic polymers [polyethylene glycol (PEG) and ethylene-diamine modified poly-isobutylene-maleic anhydride (PMA-ED)], which can encompass highly hydrophobic topoisomerase I inhibitor, SN38. Interestingly, these sheet structured GO-polymer-SN38 composites self-assembled into spherical nanoparticles in water after complexing with a hydrophilic DNA damaging drug, cisplatin. These nanoparticles showed much improved colloidal stability in water compared to their drug-loaded non-polymeric counterpart. These SN38 and cisplatin laden GO-polymer nanoparticles were taken up by HeLa cancer cells through clathrin-dependent endocytosis to home into lysosomes within 6 h, as confirmed by confocal microscopy. A combination of gel electrophoresis, flow cytometry, and fluorescence microscopy showed that these nanoparticles damaged nuclear DNA and induced topoisomerase I inhibition leading to apoptosis and finally improved HeLa cell death. These self-assembled GO-polymer nanoparticles can be used for strategic impairment of multiple cellular targets involving hydrophobic and hydrophilic drugs for effective combination therapy.